Anatomy and pollen morphology of Leymus racemosus (Lam.) Tzvelev subsp. sabulosus (Bieb.) Tzvelev and Leymus cappadocicus (Boiss. & Bal.) Melderis (Bangladesh Journal of Plant Taxonomy, 2011)
The present study aims to evaluate the anatomy of leaf and stem as well as pollen morphology in two taxa, namely L. racemosus (Lam.) Tzvelev subsp. sabulosus (Bieb.) Tzvelev and L. cappadocicus (Boiss. & Bal.) Melderis. Also, it is targeted to contribute to the morphology of these two taxa. The results have revealed varying anatomical characters in the types of stomata, wall appearance of the long cells, indumentum densities, dispositions of sclerenchyma around the vascular bundles, girders and strand shapes of the sclerenchymatic cells in the leaves, epidermal cell arrangements and epidermal cell sizes in the attachment points with sclerenchyma in the stems. Moreover, alternation in the pollen morphology concerning pollen size, operculum, undulation and the number of scabrae has also been demonstrated.Keywords: Leymus; Anatomy; Leaf; Pollen; Taxonomy.DOI: 10.3329/bjpt.v18i1.7836Bangladesh J. Plant Taxon. 18(1): 27-38, 2011 (June)